2017
DOI: 10.1017/s0007114517002161
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen generated by elemental magnesium supplementation alters rumen fermentation and microbiota in goats

Abstract: We tested the hypotheses that supplementation of a diet with elemental Mg increases ruminal dissolved H2 (dH2) in rumen fluid, which in turn alters rumen fermentation and microbial community in goats. In a randomised block design, twenty growing goats were allocated to two treatments fed the same basal diet with 1·45 % Mg(OH)2 or 0·6 % elemental Mg. After 28 d of adaptation, we collected total faeces to measure total tract digestibility, rumen contents to analyse fermentation end products and microbial groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
1
20
1
1
Order By: Relevance
“…[H] redirection toward alternative [H] sinks such as propionate. In agreement, the concentration of dissolved H 2 in the rumen has been reported to associate negatively with acetate and positively with propionate molar percentages (Wang et al, 2017(Wang et al, , 2018, although an association with propionate molar percentage was not observed in another study (Wang et al, 2016).…”
Section: The Control Of the Rumen Fermentation Profilementioning
confidence: 58%
See 1 more Smart Citation
“…[H] redirection toward alternative [H] sinks such as propionate. In agreement, the concentration of dissolved H 2 in the rumen has been reported to associate negatively with acetate and positively with propionate molar percentages (Wang et al, 2017(Wang et al, , 2018, although an association with propionate molar percentage was not observed in another study (Wang et al, 2016).…”
Section: The Control Of the Rumen Fermentation Profilementioning
confidence: 58%
“…A factor potentially masking the effects of H 2 gas added to microbial cultures headspace is lack of equilibrium with dissolved H 2 (Wang et al, 2016). In that regard, two in vivo studies in which dissolved H 2 was indirectly delivered through the reaction of elemental magnesium (Mg) with water, reported decreases in total VFA concentration as a result of the augmented dissolved H 2 concentration (Wang et al, 2017;Ma et al, 2019), although the limitations of VFA concentration as a metric of rumen fermentation pointed out above are again acknowledged.…”
Section: Effects Of Dihydrogen Accumulation On the Rates Of Fermentatmentioning
confidence: 99%
“…This may be one of the reasons why a 4.5% licorice root extract supplementation reduced the ratio of acetate to propionate in the present study. The fluctuation of pH may reflect an interaction between feed intake, urea recycling from magnesium and acid production in the rumen [25] (Wang et al, 2017). It is worth noting that in the present study, the rumen liquor was sampled for one single day, and the results should be treated with caution.…”
Section: Discussionmentioning
confidence: 99%
“…After total collection, CH 4 emissions were measured for 2 d per goat by moving each goat into a respiration chamber as described by Wang et al [13]. As only three chambers were available, it took 6 d (from d 20 to 25) to complete the measurements for all goats.…”
Section: Methodsmentioning
confidence: 99%
“…Rumen contents were collected at 0, 2.5 and 6 h after morning feeding on 2 consecutive days (d 26 and d 27) using an oral stomach tube according to Wang et al [13]. About 150 mL of rumen contents were rapidly collected after discarding the initial 100 mL of rumen contents.…”
Section: Methodsmentioning
confidence: 99%